Gender stereotypes : A content analysis of the EFL textbook speak your mind 1. (2024)
In this thesis, a detailed analysis of the content of the textbook EFL Speak Your Mind 1 was carried out using the methodology proposed by Krippendorf in 2012. To conduct the analysis, the first step was to consider the process of textbook selection at the National Pedagogical Institute: this stage allowed for an understanding of the criteria and procedures employed in the adoption of educational materials at this institution. Subsequently, a quantitative analysis of the book was conducted, evaluating the distribution of topics, activities, and the frequency and diversity of examples presented. In parallel, a qualitative analysis was carried out focusing on gender representations, identifying how gender roles and stereotypes are presented in the activities, illustrations, and texts of the book. The results of these analyses revealed both strengths and areas for improvement regarding gender representation in the educational material; consequently, an evaluation rubric for school textbooks was developed, not only to English textbooks but also to Spanish and other language textbooks, providing a standardized and objective method for evaluating pedagogical quality, representativeness, and gender equity in educational materials. In summary, this thesis offers a comprehensive evaluation of the textbook EFL Speak Your Mind 1 and contributes a practical tool for improving the selection and evaluation of educational resources, promoting more inclusive and equitable education in educational institutions in Colombia.